Desain Turbin Angin Darrieus Hellical untuk Alternatif Pengisian Daya pada Mobil Listrik - Andries Reff Onsu; Stenly Tangkuman; Hengky Luntungan (JURNAL POROS TEKNIK MESIN UNSRAT, 2021)
When the car moves forward, the air flowing through it will be left behind. By placing a wind turbine on a car, the air flow can be used to rotate the turbine. The addition of tunnels and turbines on the car will change the aerodynamic force, so that it will change the amount of power the car needs. To analyze this, modeling and simulation were carried out. The modeling software used is SolidWorks 2013 Premium and the simulation software is Ansys Workbench 18.1. This study uses three car models, namely: conventional car models, cars with front tunnels and cars with rear tunnels. Making tunnels and installing turbines affect the aerodynamic forces. The aerodynamic force of the car after the turbine installed is smaller than the aerodynamic force of the car before the turbine installed for the car mode of rear turbine modification, while for the car model of front turbine modification, the aerodynamic force of the car after the turbine installed is greater than the aerodynamic force of the car after the turbine installed. The dimensions of the Darrieus helical wind turbine are 0.3 m in height, 0.2 mm in diameter, the blade profile uses NACA 0021, and the blade length is 0.03 m with a helical angle of 50Âº. At a car speed of 100 km/h, it is obtained Cp of 0.55 with a power of 60.2 Watt for the wind turbine installed in the rear tunnel car, while for the wind turbine mounted on the front tunnel car, it obtained Cp of 0.26 with a power of 3.903 Watt.